Eosinophilic esophagitis and other non-reflux esophageal disorders - Katzka, David (Henry Stewart Talks, 2011)
Eosinophilic esophagitis, Mechanisms of allergy-induced esophagitis, Risk of esophageal ring and stricture formation, Effect of steroids on allergy-based esophagitis, Safety and efficacy of dilation of eosinophilic esophagitis strictures, Pathogenesis of inflammation and fibrosis in eosinophilic esophagitis